2017
DOI: 10.1002/humu.23232
|View full text |Cite
|
Sign up to set email alerts
|

The influence of SNP-based chromosomal microarray and NIPT on the diagnostic yield in 10,000 fetuses with and without fetal ultrasound anomalies

Abstract: Prenatal diagnostics has been impacted by technological changes in the past decade, which have affected the diagnostic yield. The aim of this study was to evaluate the impact of SNP array and noninvasive prenatal testing (NIPT) on the diagnostic yield and the number of invasive tests in our center. The frequency of pathogenic fetal unbalanced chromosome aberrations was studied in 10,005 cases referred for prenatal testing in 2009-2015. Chromosomal SNP microarray analysis replaced karyotyping in all invasively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 39 publications
3
35
1
Order By: Relevance
“…Grati et al (2017) reported that the following risks of finding a mosaicism in CVS after a positive cfDNA result: 2% for T21, 4% for T18 and 22% for T13. While cfDNA testing is highly sensitive and specific, false positive results can occur and therefore positive results should be confirmed with invasive testing .…”
Section: Chromosomal Abnormalitiesmentioning
confidence: 99%
“…Grati et al (2017) reported that the following risks of finding a mosaicism in CVS after a positive cfDNA result: 2% for T21, 4% for T18 and 22% for T13. While cfDNA testing is highly sensitive and specific, false positive results can occur and therefore positive results should be confirmed with invasive testing .…”
Section: Chromosomal Abnormalitiesmentioning
confidence: 99%
“…The most common incidental findings were X-Linked Ichtyosis (OMIM #308100; 13 cases, six females and seven males), Hereditary Neuropathy with liability to Pressure Palsies (OMIM #162500; six cases), and Charcot-Marie-Tooth type 1A (OMIM #118200; five cases) (Table 1 and Table S3).Susceptibility CNVs were diagnosed in 1.6% (210/13 266) of our population; based on our national guidelines (see Vanakker et al and Section 4), one third of those (71/210 or 33.8%; 0.5% of the total population) were reported(Table S1). In cases with an ultrasound anomaly, 0.7% carried a reported susceptibility CNV; this was not significantly different compared with the prevalence in the entire prenatal population, in accordance with the fact that susceptibility CNVs are rarely associated with ultrasound anomalies.Table 1shows the most frequent susceptibility CNVs: the 22q11.2 duplication syndrome (OMIM #608363; 24 cases) and the 15q11.2 BP1-BP2 duplication17 (32 cases) are respectively the most common reported and unreported susceptibility CNV. Susceptibility CNVs were all cryptic.The overall added diagnostic value of using CMA compared with karyotyping was 1.8%.…”
mentioning
confidence: 99%
“…In the case of ultrasound anomalies, we observed a 4% difference (18.1% vs 22.1%) in the diagnostic yield of NIPT versus CMA (Table 2), clearly demonstrating that NIPT cannot replace CMA for this indication. With respect to the implementation of NIPT for pregnancies without ultrasound anomalies, concerns have also been raised, as subchromosomal pathogenic CNVs will be missed 32,33. In our population, 26.2% (83/317) of reported CNVs below 10 Mb were found in cases with the indication "an aberrant Down syndrome screening test," "advanced maternal age," or "other indications," all of which would have remained undetected with NIPT as the first-tier test, even when assuming a resolution similar to that of karyotyping.…”
mentioning
confidence: 99%
“…Future prospective studies will be needed to test in larger sample size, and prior to or in parallel with current NGS-or microarray-based PGS testing in order to better estimate the test performance statistics (23). Nonetheless, in the evolution of methods to better assess chromosomal copy number in the preimplantation embryo, from FISH to microarray and NGS (24)(25)(26), nanopore-based sequencing has the potential to offer rapid testing results within an IVF lab setting.…”
Section: Discussionmentioning
confidence: 99%